The functional diversity of fishes in a Neotropical reservoir based on intraspecific trait variability: trends on community assembly rules and biological invasions. - Alves, Jonas Campaner (2024)
An essential question in ecology relies on whether to analyze functional diversity through species traits or to explore the traits' variability at the individual level. Traditionally, several studies have been based on unique values to represent species traits, assuming that intraspecific trait variation (ITV) has minimal impact on overall community trait variability. However, ITV can significantly influence assessments of individual and species adaptation to environmental disturbances, providing insights concerning density patterns, speciation, dispersal, and biological interactions. Thus, the importance of ITV was assessed from two perspectives: (i) community assembly rules and (ii) biological invasions. A dataset comprising ten morphological traits related to habitat use and diet of 5226 fishes belonging to 49 species that occupy the marginal areas of the Itaipu Reservoir (Brazil) was used as a case study. First, the relative contributions of ITV and species turnover (interspecific variability) to overall trait variability and the strength of internal and external filters on fish assemblages using individual traits were investigated. Species turnover accounted for most trait variance within assemblages, but ITV also played an important role for specific traits. Internal filters such as competition highly influence the functional diversity of fish species in an old reservoir. Alternatively, external filters (i.e., regional processes) did not present significant effects on functional traits, which may be related to their greater influence during the reservoir's filling phase. The difference between the functional niche occupied by native species and non-native ones, and the impact of non-native species dominance on the functional diversity patterns of native assemblages (indexed by functional richness, functional evenness, functional divergence, and functional redundancy) was also investigated. It was observed that the functional niche occupied by native species differs from non-native species, suggesting that non-native species have traits that enable them to exploit resources differently. Non-native species presented negative effects on the functional attributes of native fish populations, even in highly impacted environments such as reservoirs, reinforcing the importance of understanding the dynamics between native and non-native species in specific ecosystems. It is expected that the results of this study will assist in the development of public policies in the area of reservoir conservation, offering new insights into critical mechanisms associated with the biodiversity of the marginal regions of reservoirs that are exploited by human activities.